The Impact of Product Quality and Brand Image on Customer Loyalty of Tolak Angin Through Consumer Satisfaction as an Intervening Variable (A Study on Sidomuncul Products Consumers in Samarinda) - Desi Caprianti; Eddy Soegiarto; Eka Yudhyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of product quality, brand image, and customer satisfaction on customer loyalty for Sido Muncul products, a leading herbal medicine producer in Indonesia known for products like Tolak Angin and Kuku Bima Ener-G! The research utilizes Partial Least Squares (PLS) methodology to analyze data collected from 190 respondents, categorized by gender, age, occupation, and purchase frequency. The analysis demonstrates that product quality significantly influences customer satisfaction (path coefficient 0.88; t-statistic 36.224), and customer satisfaction significantly impacts customer loyalty (path coefficient 0.721; t-statistic 7.104). However, brand image does not significantly affect customer satisfaction (path coefficient 0.021; t-statistic 0.637). The model explains 78.6% of the variation in customer satisfaction and 75.1% in customer loyalty, with a predictive relevance (Q²) of 0.947. The study is limited by its sample size and the specific focus on Sido Muncul products, which may affect the generalizability of the results to other industries or brands. The findings suggest that companies should prioritize enhancing product quality and ensuring customer satisfaction to foster customer loyalty, rather than focusing on brand image alone. This research contributes to the understanding of the relative importance of product quality and customer satisfaction in influencing customer loyalty, with specific insights into the herbal medicine industry in Indonesia.